Characteristics of bioplastic made from modified cassava starch with addition of polyvinyl alcohol. Issue 1 (November 2020) - Syamani, F A; Kusumaningrum, W B; Akbar, F; Ismadi,; Widyaningrum, B A; Pramasari, D A
Abstract: Food packaging plastic from petroleum-based sources can be a problem to the environment due to its non-biodegradability. The development of bioplastic from modified cassava-starch will be an alternative to overcome that problem. Since starch-based bioplastic usually has low mechanical strength and damage if exposed to water, it's modification with polyvinyl alcohol (PVA) and citric acid is necessary. Bioplastics are made by heating a solution of modified cassava starch at 75 °C for 1 hour. After starch solution was gelatinized, glycerol (5% based on starch weight) was added, and then PVA solution (25, 50, 100% based on starch weight) was inserted gradually. While stirring was continued, citric acid (5% based on starch weight) was added into the solution. The bioplastic solution was then poured into a 20 × 20 cm acrylic sheet and cooled at room temperature for 3 days, so that the bioplastic sheet was ready for mechanical strength test (ASTM D 882-75b Tensile Properties of Thin Plastic Sheeting) and for thermal properties test with Thermo Gravimetric Analyzer. The results suggested that the addition of 25% polyvinyl alcohol (PVA) into bioplastic made from modified cassava starch produced bioplastic with higher tensile strength compare to that without PVA addition. On the other hand, the addition of 100% PVA could slightly increase bioplastic elongation. The decomposition temperature of bioplastic made from modified cassava starch with 50% PVA was higher than that of the bioplastic without PVA addition, indicated that bioplastic with 50% PVA was more thermally stable.